Seni Kriya sebagai Modal Sosial dan Ekonomi: Tantangan dan Peluang bagi Masyarakat Pengrajin - Haryono Haryono; Qatrunnada Qatrunnada (SENTRI: Jurnal Riset Ilmiah, 2026)
Seni kriya is one form of cultural heritage that plays a strategic role in the life of artisan communities, not only as an aesthetic expression but also as social and economic capital. This study aims to analyze the role of seni kriya in building the social capital of artisan communities, identify its contribution to improving the local economy, and examine the challenges and opportunities faced in its development. The research approach used is descriptive qualitative with a case study method. Data were obtained through participatory observation, in-depth interviews with seni kriya artisans, community leaders, and policymakers, as well as documentation and literature review. The results show that seni kriya functions as social capital through the strengthening of social networks, mutual cooperation values, and the collective cultural identity of artisan communities. Economically, seni kriya contributes to the creation of alternative sources of income and encourages the growth of a locally based creative economy. However, the development of seni kriya still faces various challenges, such as limited innovation among artisans, access to capital, marketing constraints, and low interest among the younger generation. On the other hand, development opportunities are available through the integration of seni kriya with tourism, the utilization of digital technology, and government policy support. This study is expected to provide strategic recommendations for strengthening seni kriya as sustainable social and economic capital for artisan communities.